2022
DOI: 10.1371/journal.pone.0276855
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and barriers in the implementation of ultrasound-based assessment of muscle mass in Japan: A nationwide, web-based cross-sectional study

Abstract: Muscle mass is an important factor for surviving an illness. Ultrasound has gained increased attention as a muscle mass assessment method because of its noninvasiveness and portability. However, data on the frequency of ultrasound-based muscle mass assessment are limited, and there are some barriers to its implementation. Hence, a web-based cross-sectional survey was conducted on healthcare providers in Japan, which comprised four parts: 1) participant characteristics; 2) general muscle mass assessment; 3) ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a survey-based study in Japan that investigated the barriers to implementing US as a tool to measure muscle mass indicated that 21% of healthcare practitioners conduct US-based muscle mass measurements, whereas only 6% of dietitians use US for muscle mass assessment. 35 The authors of the Japanese study also reported that the greatest barrier to the implementation and use of US is lack of education. 35 Lack of standardized protocols for assessing muscle mass by ultrasound might be an additional challenge.…”
Section: Practicality and Challenges Of Using Us As A Nutritional Ass...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey-based study in Japan that investigated the barriers to implementing US as a tool to measure muscle mass indicated that 21% of healthcare practitioners conduct US-based muscle mass measurements, whereas only 6% of dietitians use US for muscle mass assessment. 35 The authors of the Japanese study also reported that the greatest barrier to the implementation and use of US is lack of education. 35 Lack of standardized protocols for assessing muscle mass by ultrasound might be an additional challenge.…”
Section: Practicality and Challenges Of Using Us As A Nutritional Ass...mentioning
confidence: 99%
“… 35 The authors of the Japanese study also reported that the greatest barrier to the implementation and use of US is lack of education. 35 Lack of standardized protocols for assessing muscle mass by ultrasound might be an additional challenge. 36 As this can result in variations in measurement techniques and inconsistency in reporting findings.…”
Section: Practicality and Challenges Of Using Us As A Nutritional Ass...mentioning
confidence: 99%
“…Moreover, the availability of US devices and appropriate training of medical staff in measuring skeletal muscle mass using sonography are further determinants for the implementation in routine clinical practice. 45,47 Current recommendations and latest evidence on protein dosing in MNT Adequate protein supply within an energy-balanced MNT is of particular importance in the critical care setting to stimulate muscle protein synthesis, reduce muscle protein breakdown, and limit amino acid oxidation after disease-related alterations in substrate utilization and metabolism. 48 Besides targeted medication and exercise, protein intake higher than the amount…”
Section: Protein Metabolism In Critical Illnessmentioning
confidence: 99%
“…International, standardized protocols are required to assess qualitative muscle changes during the ICU stay of patients at high risk for developing neuromuscular acquired weakness (ICUAW), also taking into account method‐inherent limitations (eg, reliability may be affected by the fluid status and position of the patients when performing measurements). Moreover, the availability of US devices and appropriate training of medical staff in measuring skeletal muscle mass using sonography are further determinants for the implementation in routine clinical practice 45,47 …”
Section: Protein: What Is the Optimal Dosage?mentioning
confidence: 99%
“…Ultrasonography-based muscle mass assessment is applied in acute [19] or chronic diseases [20]; however, it is not widely used owing to a lack of technical skills. In a previous questionnaire survey, ultrasonography-based muscle mass assessment was conducted only in 14% of health care workers [21].…”
Section: Introductionmentioning
confidence: 99%